Exonic versus intronic SNPs: contrasting roles in revealing the population genetic differentiation of a widespread bird species - Zhan, X; Dixon, A; Batbayar, N; Bragin, Evgeny A.; Ayas, Z; Deutschova, L (Heredity, 2014)
Recent years have seen considerable progress in applying single nucleotide polymorphisms (SNPs) to population genetics studies. However, relatively few have attempted to use them to study the genetic differentiation of wild bird populations and none have examined possible differences of exonic and intronic SNPs in these studies. Here, using 144 SNPs, we examined population genetic differentiation in the saker falcon (Falco cherrug) across Eurasia. The position of each SNP was veriﬁed using the recently sequenced saker genome with 108 SNPs positioned within the introns of 10 fragments and 36 SNPs in the exons of six genes, comprising MHC, MC1R and four others. In contrast to intronic SNPs, both Bayesian clustering and principal component analyses using exonic SNPs consistently revealed two genetic clusters, within which the least admixed individuals were found in Europe/central Asia and Qinghai (China), respectively. Pairwise D analysis for exonic SNPs showed that the two populations were signiﬁcantly differentiated and between the two clusters the frequencies of ﬁve SNP markers were inferred to be inﬂuenced by selection. Central Eurasian populations clustered in as intermediate between the two main groups, consistent with their geographic position. But the westernmost populations of central Europe showed evidence of demographic isolation. Our work highlights the importance of functional exonic SNPs for studying population genetic pattern in a widespread avian species.
Keywords: Aves; Falco cherrug; Falconidae; genetic marker